(untitled) (Communications in Computational Physics, 2018)
In this paper, we present a detailed numerical implementation of the multicomponent potential theory of adsorption which is among the most accurate gas mixtures adsorption models. The implementation uses the NIST Refprop database to describe fluid properties and applies to pure gases and mixtures in both subcritical and supercritical regimes. The limitations of the model and the issues encountered with its implementation are discussed. The adsorption isotherms of CH4/CO2 mixture are modeled and parameterized as implementation examples.